Induction of Cold Hardiness in an Invasive Herbivore: The Case of Hemlock Woolly Adelgid (Hemiptera: Adelgidae). Issue 1 (8th February 2017) - Elkinton, Joseph S.; Lombardo, Jeffrey A.; Roehrig, Artemis D.; McAvoy, Thomas J.; Mayfield, Albert; Whitmore, Mark
Abstract : As a measure of cold hardiness, we tested the supercooling points or freezing temperatures of individual hemlock woolly adelgids ( Adelges tsugae Annand) collected from 15 locations across the north to south range of the adelgid in eastern North America at different times during two winters. Adelgids from the northern interior locations with USDA hardiness zones of 5B–6B had lower supercooling points than adelgids from more southern or more coastal locations (zones 7A and 6B), where minimum winter temperatures were higher. Supercooling points reached a minimum in February in northern but not in southern locations. Laboratory experiments demonstrated that adelgids exposed to colder temperatures (−12 °C) had lower supercooling points after 3 d and adelgids held at 10 °C had higher supercooling points than did adelgids held at 2 °C for the same period. Extending these periods to 7 d produced no further change in supercooling points. Adelgids at northern sites had much lower supercooling points in February 2015 following at least 10 d of much colder weather than adelgids from those same sites in February 2016 following much warmer weather. The induction of cold hardiness produced much year-to-year variation in cold hardiness, especially in northern sites, in addition to concurrently and previously demonstrated genetic differences in cold hardiness between northern and southern adelgid populations. Consequently, the cold temperatures required to kill hemlock woolly adelgids will vary year to year and week to week based on exposure to prior temperatures.